2001
DOI: 10.1002/1098-2795(20010401)58:4<432::aid-mrd11>3.3.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose pretreatment for enucleation: An efficient and non‐damage method for removing the spindle of the mouse MII oocyte

Abstract: Oocytes enucleated at metaphase II stage can support reprogramming of transferred nucleus and further developing to term. However, the first polar body in mice sometimes migrates away from the original place of expulsion, so the chromosomes of the oocyte will displace from the first polar body. Thus, it is not always possible to successfully enucleate according to the position of the first polar body. Here we use sucrose treatment to visualize metaphase spindle fibers and chromosomes with standard light micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 21 publications
4
19
0
Order By: Relevance
“…It is important to point out that the sucrose-induced shrinkage of the oocytes does not significantly reduce the viability of the oocytes or the subsequent development of the embryos, as shown by our studies [10,11,24,25] and by those of others [18-23, 26, 27]. The electrolyte NaCl, on the other hand, has a deleterious effect on the viability of oocytes and is not suitable for the induction of projection for purposes of micromanipulation [31,32].…”
Section: Discussionsupporting
confidence: 43%
See 3 more Smart Citations
“…It is important to point out that the sucrose-induced shrinkage of the oocytes does not significantly reduce the viability of the oocytes or the subsequent development of the embryos, as shown by our studies [10,11,24,25] and by those of others [18-23, 26, 27]. The electrolyte NaCl, on the other hand, has a deleterious effect on the viability of oocytes and is not suitable for the induction of projection for purposes of micromanipulation [31,32].…”
Section: Discussionsupporting
confidence: 43%
“…We surmised that such treatment of oocytes could induce or enhance the possibility of the spindle undergoing changes distinct from those of other cytoplasmic components. However, systematic analyses to test this hypothesis remained to be performed [10]. Here, we examined the factors responsible for inducing changes in the spindle area of mouse MII oocytes, and we found that hypertonic sucrose, not serum or standard media, is important for the swelling of the spindle area and the formation of projections.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This somatic cell nuclear transfer manipulation was a combination of the Roslin technique and the Honolulu technique [14,15]; after culture under serum-starvation culture, a 3 h post-electrofusion interval and strontium activation were adopted. The nuclear transfer manipulation solution is CZB medium supplemented with 3% sucrose, 10% FCS, and 5 Ag/ml cytochalasin B [16]. The CZB culture medium free of glucose was used for early embryo development [15,17].…”
Section: Mouse Intraspecies/interspecies Nuclear Transfermentioning
confidence: 99%